DOES ISLAMIC BANKING PROMOTE FINANCIAL INCLUSION AMONG WOMEN IN OIC MEMBER COUNTRIES? (International Journal of Islamic Business, 2022)
Previously, women in Organization of Islamic Cooperation (OIC) member countries were reported to be more financially excluded compared to the global average. Hence, this study aims to have a closer look at the aspect of gender inequality in financial inclusion in OIC member countries. Specifically, it seeks to examine the role of Islamic banking in enhancing financial inclusion among women in selected OIC member countries empirically. This study frames its analysis based on annual economic and financial data for OIC member countries from several sources including the World Bank Global Findex and World Development Indicators for each respected country for the years 2011 and 2014 using ordinary least squares (OLS) estimation. The findings show significant improvement in the growth of women’s account penetration for 2014, suggesting Islamic banking deepening has had a positive effect on financial inclusion among women in the OIC member countries under study. The significant positive effect of Islamic banking presence and accessibility of Muslim women to financial services indicates pivotal role of Islamic banking in promoting financial inclusion among women, enhance economic activities for women and reduce gender gap in finance. The finding helps to promote gender equality, empowerment and financial inclusion among Muslim women in OIC countries through Islamic banking services. The findings call for Islamic finance industry players to expand their outreach to Muslim clients and help policymakers to define their role more clearly in expanding financial inclusion, Islamic or otherwise, to Muslim adults.